Pielonefritis - Hamzah, Nashir (CV RIFAINSTITUT, 2022)
Pyelonephritis is a type of urinary tract infection (UTI) that generally begins in the urethra or bladder and spreads to one or both kidneys. In the United States, the incidence of acute pyelonephritis is 250,000 visits and 200,000 hospitalizations annually. The clinical manifestations of acute pyelonephritis consist of fever (> 38°C), chills, low back pain, and pain. Patients with complicated acute pyelonephritis may have sepsis and acute kidney diseases (AKI). 1,2,4 To establish the diagnosis of pyelonephritis requires laboratory examination and radiological imaging, such as ultrasound, whether or not using contrast. Once diagnosed, pyelonephritis should be treated promptly, initially with empiric antimicrobial therapy and then continued according to the bacteria detected in the urine